Histopathological lesions and bacteriological isolation in apparently healthy gamitanas (Colossoma macropomum) - Ramos E., Fernando (2016)
The aim of this study was to determine histopathological lesions and bacterial isolates in organs and tissues of clinically healthy gamitanas (Colossoma macropomum). Forty juveniles were collected from a fish farm in the region of Ucayali, Perú. Samples were collected from kidney, liver, spleen, stomach, gills and muscle for histopathological and bacteriological analysis. In the liver was found hydropic degeneration (39/40), in kidney, hydropic degeneration and tubular necrosis (40/40) with an increase of melanomacrophage centres in the periphery of the tubules, in stomach, hyaline degeneration (25/40), and in gills, infiltration of inflammatory cells in branchial filament (40/40), interlamellar epithelium hyperplasia (40/40) and hyperplasia in branchial filament (18/40). No lesions were found in the spleen. Myxosporean parasites were found in gills (2/40), kidney (40/40) and muscle (12/40), and monogenean parasites in gills (6/40). Bacteria were isolated in low frequency, including potentially pathogenic bacteria (Aeromonas hydrophila and Edwardsiella tarda) in gills and organs, but without association with the histopathological findings.